PENDEKATAN KECERDASAN EMOSIONAL; IMPLEMENTASI DALAM PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA ARAB SISWA MADRASAH ALIYAH - Oktavia Ratnaningtyas (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2019)
Speak of skills an Arabic Language is a basic skill whose main goal is being able to communicate with others, one of the approaches used in teaching speaking Arabic is the approach to emotional intelligence, for students at the Cukir Jombang Mu'allimat College Madrasah Aliyah. The curriculum in teaching speaks Arabic refers to K13 based on RI Minister of Education regulation No. 21 of 2016, which is combined with the tourism curriculum developed by Madrasas which refers to Permenag No. 2 of 2008. The teacher uses this emotional intelligence approach as a solution to problems in teaching speaking Arabic in terms of the approach used in teaching and learning activities. With this approach to emotional intelligence students have a high sense of optimism and motivation in learning Arabic speaking skills. Also, with this approach students are able to recognize emotions themselves so they can manage emotions and use emotions productively, and can recognize the emotions of others (empathy) so they can foster relationships to communicate well.